2014
DOI: 10.1017/s1368980014003024
|View full text |Cite
|
Sign up to set email alerts
|

Food neophobia associates with lower dietary quality and higher BMI in Finnish adults

Abstract: Objective: Food neophobia has been associated with decreased consumption of vegetables mainly among children. We hypothesized that food neophobia in adults is also associated with lower overall dietary quality and higher BMI. Design: Data for the present cross-sectional analyses were derived from parents in a follow-up family study. Setting: The STEPS study, a longitudinal study of health and development of a cohort of children born in south-west Finland. Subjects: The parents, 1178 women (age 19-45 years, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
53
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 42 publications
17
53
3
2
Order By: Relevance
“…These differences, however, disappeared in children aged 8 and 9 years, suggesting 326 that with increasing age, differences in FN due to gender may decrease. In adults, gender-related differences 327 in FN are not found (Knaapila et al, 2015) or rarely found and when they are, the differences are marginal 328 A weak, negative association between FN and the age of introduction of semi-solids in children's diet was 343 seen in our data. In line with our finding, Robinson et al (2007) showed that poorer-quality diets (i.e., less 344 fruit, vegetable and wholegrain products) of young children (6-12 months) were more common in families 345 where solid foods were introduced at an earlier age.…”
Section: Discussion 290mentioning
confidence: 55%
See 1 more Smart Citation
“…These differences, however, disappeared in children aged 8 and 9 years, suggesting 326 that with increasing age, differences in FN due to gender may decrease. In adults, gender-related differences 327 in FN are not found (Knaapila et al, 2015) or rarely found and when they are, the differences are marginal 328 A weak, negative association between FN and the age of introduction of semi-solids in children's diet was 343 seen in our data. In line with our finding, Robinson et al (2007) showed that poorer-quality diets (i.e., less 344 fruit, vegetable and wholegrain products) of young children (6-12 months) were more common in families 345 where solid foods were introduced at an earlier age.…”
Section: Discussion 290mentioning
confidence: 55%
“…Thus, FN could potentially lead to important 37 nutritional consequences (Zickgraf and Schepps, 2016;Jaeger et al, 2017). It is largely recognized that FN is 38 negatively related to daily intake and liking of fruit and vegetables (Perry et and increased body mass index (BMI) has been observed in adults (Knaapila et al, 2015;Proserpio et al, 43 2018). Neophobic individuals may choose to eat familiar foods which are more energy dense than fruits and 44 vegetables (Knaapila et al, 2011) or may be less willing to try healthy alternative versions of familiar products 45 (Laureati et al, 2015b).…”
Section: Introduction 28mentioning
confidence: 99%
“…Food neophobia is associated with several factors, including age, gender, personality features, living area, education level, and socioeconomic status (3)(4)(5)(6)(7). Furthermore, a high prevalence of food neophobia has been detected in children in particular and in people with low socioeconomic status living in rural areas (8,9). To some extent, food neophobia in children can be considered a normal and developmentally appropriate response characterized as "omnivore's dilemma," in which the sampling of new food items may provide a source of nutrition or toxicity, thus potentially resulting in neophobic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Food neophobia is also associated with the development of other eating disorders and a reduced intake of fish and vegetables, leading to reduced overall dietary quality (4,9). Previously, reduced dietary quality has been associated with an increased risk of obesity and subsequent chronic diseases [e.g., cardiovascular disease (CVD), coronary heart disease (CHD), and type 2 diabetes (T2D)] and inflammation (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation